Efficacy Of Ayurvedic Medicine And Yoga On Childhood Asthma W.S.R. To Tamaka Shwasa - Gupta, Nandini; Verma, Mithilesh Kumar (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda is the major systems of indigenous medicines and treatment. In ancient different kinds of Ayurvedic medicines were discovered after continuous study like as observations, experiments, trials and conclusions. Bronchial Asthma occurs due to many cause e.g. environmental, racial, and behavior... Tamaka Shwasa is disease according to Ayurvedic texts that shows close resemblance with bronchial asthma on the basis of clinical manifestations. There is no cure for Asthma as per the Conventional Medical Science. Ayurvedic medicines can be a potential and effective alternative for the treatment against the bronchial asthma. Ayurvedic medicines are used for the treatment of disease globally so that people all over the world can can keep faith on it on the basis of scientific evidences. The present study was a review on the management of Tamaka- Shwasa (bronchial asthma) through Ayurvedic approach that includes a combination of Ayurvedic drugs in Shodhana and Shamana chikitsa and lifestyle management. Ayurvedic drugs include the respiratory tonics and naturally occurring bronchodilator and immune- modulator. Thus, study concluded that the Shodhana, Shamana, herbal and herbo-minerals compound drug has got significant anti asthmatic properties.